PTEN Mutations as a Cause of Constitutive Insulin Sensitivity and Obesity - Pal, Aparna; Barber, Thomas M; Van de Bunt, Martijn; Rudge, Simon A; Zhang, Qifeng; Lachlan, Katherine L; Cooper, Nicola S; Linden, Helen; Levy, Jonathan C; Wakelam, Michael J.O; Walker, Lisa; Karpe, Fredrik; et al. (The New England journal of medicine, 2012)
Evidence suggests that protection against cancer confers a risk of type 2 diabetes and vice versa. This study shows that persons susceptible to cancer owing to a constitutive mutation in the tumor-suppressor gene PTEN also have heightened sensitivity to insulin and are obese. Epidemiologic evidence for a link among type 2 diabetes, obesity, and cancer has increased interest in the idea that some antidiabetes therapies may increase the risk of susceptibility to cancer, whereas others appear to offer protection. 1 Such a link is also supported by the discovery of several susceptibility loci for type 2 diabetes and their unexpected proximity to genes implicated in cell-cycle regulation. 2 The discovery of common genetic variants that influence both the risk of cancer and the risk of type 2 diabetes, in opposite directions, suggests that the two conditions may result from defects in the same pathway. 3 – . . .